Early Trauma-Induced Coagulopathy is Associated with Increased Ventilator-Associated Pneumonia in Spinal Cord Injury Patients. Issue 5 (May 2016) - Younan, Duraid; Lin, Erica; Griffin, Russell; Vanlandingham, Sean; Waters, Alicia; Harrigan, Mark; Pittet, Jean-Francois; Kerby, Jeffrey D.
ABSTRACT: Introduction: Early trauma-induced coagulopathy may increase susceptibility to nosocomial infections such as ventilator-associated pneumonia. However, the relationship between trauma- induced coagulopathy and the development of ventilator-associated pneumonia in spinal cord injury patients has not been evaluated. Methods: We conducted a 5-year retrospective study of 300 spinal cord injury patients admitted to Level 1 trauma center. Standard coagulation studies were evaluated upon arrival, prior to fluid resuscitative efforts, and at 24 h after admission. Based on these studies, three groups of patients were identified: no coagulopathy, latent coagulopathy, and admission coagulopathy. Ventilator- associated pneumonia was identified utilizing Centers for Disease Control and Prevention criteria. Since we used the data in the trauma registry and did not have the information on FiO2 and PEEP, we elected to use the VAP terminology and not the VAE sequence. Demographic, injury, and clinical characteristics were compared among no coagulopathy, latent coagulopathy, and admission coagulopathy groups using chi-square test and ANOVA for categorical and continuous variables, respectively. A logistic regression was used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) for the association between coagulopathy and both ventilator-associated pneumonia and mortality. Results: The incidence of ventilator-associated pneumonia was 54.5% (OR 4.01, 95% CI 1.76–9.15) in spinal cord injury patients with admission coagulopathy, compared with the 17.5% in spinal cord injury patients with no coagulopathy. Mortality was significantly higher in spinal cord injury patients with admission coagulopathy than in spinal cord injury patients with no coagulopathy (OR 6.14, 95% CI 1.73–21.73). After adjusting for age, race, injury mechanism, Injury Severity Score, base deficit at admission, the number of pRBC units transfused in the first 24 h, and hospital stay, only the association of ventilator-associated pneumonia among those with admission coagulopathy remained significant (OR 3.51, 95% CI 1.48–8.32). Compared with those with no coagulopathy, patients with admission coagulopathy had a higher odds of death (4.10, 95% CI 1.53–11.02), though this association lost significance after adjustment (OR 3.56, 95% CI 0.90–14.12). There was no statistical difference in mortality for latent coagulopathy compared with no coagulopathy patients. Conclusion: Coagulopathy on admission in patients with spinal cord injury is associated with a statistically significant increase in ventilator-associated pneumonia incidence. Additional research is warranted to further characterize this association.